How often do you cheat? Dispositional influences and intrapersonal stability of dishonest behavior - Leisge, Kai; Kaczmarek, Christian; Schaefer, Sabine (Frontiers in Psychology, 2024)
Dishonesty, including lying, cheating, deception, and deviating from societal norms, has far-reaching implications across various aspects of modern society. From minor consequences like social discontent to severe outcomes such as economic damage through tax evasion, dishonest behavior affects us in multiple ways. This study investigates whether gender and psychological traits contribute to dishonest behavior, and whether unethical conduct is stable across diverse tasks. We examined 63 participants using a “Difference Spotting Task” (DST) and two motor tasks (1. coordinative throwing; 2. isometric strength). Dishonesty was measured by comparing self-reported performance with actual performance, allowing for a comprehensive analysis of both occurrence and extent of dishonesty. Our findings indicate that gender does not significantly influence the occurrence or extent of dishonest behavior. Moreover, we discovered that “Social Desirability” positively influences the extent of dishonesty, while “Task Orientation” increases the likelihood of engaging in dishonest acts. The study also reveals that the level of dishonesty remains relatively stable across all three tasks at an intrapersonal level.